Allocating scarce life-saving resources: the proper role of age. Issue 12 (22nd March 2021) - Persad, Govind; Joffe, Steven
Abstract : The COVID-19 pandemic has forced clinicians, policy-makers and the public to wrestle with stark choices about who should receive potentially life-saving interventions such as ventilators, ICU beds and dialysis machines if demand overwhelms capacity. Many allocation schemes face the question of whether to consider age. We offer two underdiscussed arguments for prioritising younger patients in allocation policies, which are grounded in prudence and fairness rather than purely in maximising benefits: prioritising one's younger self for lifesaving treatments is prudent from an individual perspective, and prioritising younger patients works to narrow health disparities by giving priority to patients at risk of dying earlier in life, who are more likely to be subject to systemic disadvantage. We then identify some confusions in recent arguments against considering age.